The Effect of Employee Development and Work Motivation on Employee Performance of PT Cahaya Adin Abadi Surabaya - Ewaldus Siuk; Rohmah Kurniawati (Information Technology and Science (ITScience), 2025)
The important role of PT Cahaya Adin Abadi Surabaya is to implement industrial revolution and industrial transformation strategies. This company is a pioneer of human resource placement services, labor recruitment, training and human resource consultants in Surabaya. Based on the background of the problem and the formulation of the problem above, the purpose of this study is to obtain clarity or to describe and analyze, to determine the extent to which the influence of employee development and work motivation together or simultaneously affects the performance of employees of PT Cahaya Adin Abadi Surabaya, to determine the extent to which the influence of employee development and work motivation respectively or partially affects the performance of employees of PT Cahaya Adin Abadi Surabaya, and to determine which of the employee development and work motivation variables has the most dominant influence on the performance of employees of PT Cahaya Adin Abadi Surabaya. In this study, the data analysis technique used Multiple Linear Regression Analysis. This model was chosen because researchers wanted to know how much influence the factors of employee development and work motivation on employee performance in the environment consisted of both simultaneously and partially. Processing the data using the SPSS Ver 21.00 program, the magnitude of the influence of employee development and work motivation on employee performance will be known. Hypothesis testing is done using statistical tests and classical assumption tests. The conclusions that can be drawn from the results of this study include: Employee Development and Work Motivation have a real influence simultaneously (together) on the performance of employees of PT Cahaya Adin Abadi Surabaya (Y), Employee Development and Work Motivation have a real influence partially (individually) on the performance of employees of PT Cahaya Adin Abadi Surabaya (Y), and Among Employee Development and Work Motivation, it turns out that employee development has a dominant influence on the performance of employees of PT Cahaya Adin Abadi Surabaya (Y), with a partial influence of 40.6%.